Veterinary epidemiology at ILRAD and ILRI, 1987–2018 - Perry, Brian D.; Bett, Bernard K.; Fèvre, Eric M.; Grace, Delia; Randolph, Thomas F. (CAB International, 2020)
This chapter describes the activities of the International Livestock Research Institute (ILRI) and its predecessor, the International Laboratory for Research on Animal Diseases (ILRAD) from 1987 to 2018. Topics include scientific impacts; economic impact assessment; developmental impacts; capacity development; partnerships; impacts on human resources capacity in veterinary epidemiology; impacts on national animal health departments and services; impacts on animal health constraints in developing countries; impacts on ILRI's research and strategy; the introduction of veterinary epidemiology and economics at ILRAD; field studies in Kenya; tick-borne disease dynamics in eastern and southern Africa; heartwater studies in Zimbabwe; economic impact assessments of tick-borne diseases; tick and tick-borne disease distribution modelling; modelling the infection dynamics of vector-borne diseases; economic impact of trypanosomiasis; the epidemiology of resistance to trypanocides; the development of a modelling technique for evaluating control options; sustainable trypanosomiasis control in Uganda and in the Ghibe Valley of Ethiopia; spatial modelling of tsetse distributions; preventing and containing trypanocide resistance in the cotton zone of West Africa; rabies research; the economic impacts of rinderpest control; applying economic impact assessment tools to foot and mouth disease (FMD) control, the southern Africa FMD economic impact study; economic impacts of FMD in Peru, Colombia and India; economic impacts of FMD control in endemic settings in low- and middle-income countries; the global FMD research alliance (GFRA); Rift Valley fever; economic impact assessment of control options and calculation of disability-adjusted life years (DALYs); RVF risk maps for eastern Africa; land-use change and RVF infection and disease dynamics; epidemiology of gastrointestinal parasites; priorities in animal health research for poverty reduction; the Wellcome Trust Epidemiology Initiatives; the broader economic impact contributions; the responses to highly pathogenic avian influenza; the International Symposium on Veterinary Epidemiology and Economics (ISVEE) experience, the role of epidemiology in ILRAD and ILRI and the impacts of ILRAD and ILRI's epidemiology; capacity development in veterinary epidemiology and impact assessment; impacts on national animal health departments and services; impacts on animal health constraints in developing countries and impacts on ILRI's research and strategy.